2014
DOI: 10.2341/12-345-l
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Wear Opposing Polished and Aged Zirconia

Abstract: Aging of dental zirconia roughens its surface through low temperature degradation. We hypothesized that age-related roughening of zirconia crowns may cause detrimental wear to the enamel of an opposing tooth. To test our hypothesis, we subjected artificially aged zirconia and reference specimens to simulated mastication in a wear device and measured the wear of an opposing enamel cusp. Additionally, the roughness of the pretest surfaces was measured. The zirconia specimens, artificially aged by autoclave, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 27 publications
1
45
1
1
Order By: Relevance
“…Previous studies found that the texture of ceramic surfaces affects wear of opposing materials (13)(14)(15)(16). The present study compared wear of standardized polished and glazed rod specimens.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies found that the texture of ceramic surfaces affects wear of opposing materials (13)(14)(15)(16). The present study compared wear of standardized polished and glazed rod specimens.…”
Section: Discussionmentioning
confidence: 91%
“…However, other studies found that wear of ceramics was greater for materials opposed to glazed ceramics than for those opposed to polished ones (12)(13)(14)(15)(16). Janyavula et al reported that material and antagonist wear was greater for glazed zirconia than for polished zirconia (13). Lawson et al reported that wear of opposing enamel was less for polished than for glazed lithium disilicate glass (LDG) ceramics (15).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to other reports on the effects of aged zirconia when in contact with enamel. 27 After artificial aging of zirconia using autoclave and testing, no significant difference between aged and untreated zirconia was observed, as it affected enamel in the same way. 27 …”
Section: Discussionmentioning
confidence: 94%
“…Although only some preliminary clinical trials on monolithic zirconia dental restorations have been published [1,4–7], in vitro studies revealed that monolithic zirconia crowns can endure the highest fracture load among all ceramic restorative systems [3,8]. In addition, laboratory testing [912] and clinical researches [5,13,14] have shown that polished zirconia causes less tooth enamel wear than glazed zirconia, whereas glazed zirconia exhibits comparable or better results than other dental ceramic materials.…”
Section: Introductionmentioning
confidence: 99%